Cerebrospinal fluid Aβ levels correlate with structural brain changes in Parkinson's disease. Issue 3 (13th February 2013) - Beyer, Mona K.; Alves, Guido; Hwang, Kristy S.; Babakchanian, Sona; Bronnick, Kolbjorn S.; Chou, Yi‐Yu; Dalaker, Turi O.; Kurz, Martin W.; Larsen, Jan P.; Somme, Johanne H.; Thompson, Paul M.; Tysnes, Ole‐Bjørn; et al.
ABSTRACT ParkWest is a large Norwegian multicenter study of newly diagnosed drug‐naïve subjects with Parkinson's disease (PD). Cognitively normal PD subjects (PDCN) and PD subjects with mild cognitive impairment (PDMCI) from this cohort have significant hippocampal atrophy and ventricular enlargement, compared to normal controls. Here, we aimed to investigate whether the same structural changes are associated with cerebrospinal fluid (CSF) levels of amyloid beta (Aβ)38, Aβ40, Aβ42, total tau (t‐tau), and phosphorylated tau (p‐tau). We performed three‐dimensional radial distance analyses of the hippocampi and lateral ventricles using the MRI data from ParkWest subjects who provided CSF at baseline. Our sample consisted of 73 PDCN and 18 PDMCI subjects. We found significant associations between levels of all three CSF Aβ analytes and t‐tau and lateral ventricular enlargement in the pooled sample. In the PDCN sample, all three amyloid analytes showed significant associations with the radial distance of the occipital and frontal horns of the lateral ventricles. CSF Aβ38 and Aβ42 showed negative associations, with enlargement in occipital and frontal horns of the lateral ventricles in the pooled sample, and a negative association with the occipital horns in PDMCI. CSF Aβ levels in early PD correlate with ventricular enlargement, previously associated with PD dementia. Therefore, CSF and MRI markers may help identify PD patients at high risk for developing cognitive decline and dementia in the course of their illness. Contrary to Alzheimer's disease, we found no associations between CSF t‐tau and p‐tau and hippocampal atrophy. © 2013 Movement Disorder Society